pH-Driven Reversible Assembly and Disassembly of Colloidal Gold Nanoparticles - Liu, Yun; Fu, Weihua; Xu, Zhongsheng; Zhang, Liang; Sun, Tao; Du, Mengmeng; Kang, Xun; Xiao, Shilin; Zhou, Chunyu; Gong, Mingfu; Zhang, Dong (Frontiers in Chemistry, 2021)
Owing to the localized surface plasmon resonance (LSPR), dynamic manipulation of optical properties through the structure-evolution of plasmonic nanoparticles has been intensively studied for practical applications. This paper describes a novel method for direct reversible self-assembly and dis-assembly of Au nanoparticles (AuNPs) in water driven by pH stimuli. Using 3-aminopropyltriethoxysilane (APTES) as the capping ligand and pH-responsive agent, the APTES hydrolyzes rapidly in response to acid and then condenses into silicon, on the contrary, the condensed silicon can be broken down into silicate by base, which subsequently deprotonate the APTES on AuNPs. By controlling condensation and decomposition of APTES, the plasmonic coupling among adjacent AuNPs could be reversible tuned to display the plasmonic color-switching. This study provides a facile and distinctive strategy to regulate the reversible self-assembly of AuNPs and it also offers a new avenue for other plasmonic nanoparticles to adjusting plasmonic properties via reversible self-assembly.